1999
DOI: 10.1128/jvi.73.1.140-151.1999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza A Virus Replication by Compounds Interfering with the Fusogenic Function of the Viral Hemagglutinin

Abstract: Several compounds that specifically inhibited replication of the H1 and H2 subtypes of influenza virus type A were identified by screening a chemical library for antiviral activity. In single-cycle infections, the compounds inhibited virus-specific protein synthesis when added before or immediately after infection but were ineffective when added 30 min later, suggesting that an uncoating step was blocked. Sequencing of hemagglutinin (HA) genes of several independent mutant viruses resistant to the compounds re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 61 publications
2
37
0
Order By: Relevance
“…The HA 2 -F3L residue change selected under 6c was previously identified by Daniels et al (1985) in an Amtresistant avian A/H7N1 virus (Weybridge strain), which manifested an increase in hemolysis pH of 0.4 pH units. The HA 2 -F3L mutation was also reported by Plotch et al (1999), who selected a virus for resistance to the small molecule fusion inhibitor CL-61917, starting from an Amt-resistant A/FM/47 virus. The increased fusion pH of the HA 2 -F3L mutant virus is not unexpected, since this residue lies in the hydrophobic fusion peptide of HA.…”
Section: Discussionmentioning
confidence: 63%
“…The HA 2 -F3L residue change selected under 6c was previously identified by Daniels et al (1985) in an Amtresistant avian A/H7N1 virus (Weybridge strain), which manifested an increase in hemolysis pH of 0.4 pH units. The HA 2 -F3L mutation was also reported by Plotch et al (1999), who selected a virus for resistance to the small molecule fusion inhibitor CL-61917, starting from an Amt-resistant A/FM/47 virus. The increased fusion pH of the HA 2 -F3L mutant virus is not unexpected, since this residue lies in the hydrophobic fusion peptide of HA.…”
Section: Discussionmentioning
confidence: 63%
“…Although the HA has been extensively studied from a biochemical and epidemiological perspective, specific antiviral drugs blocking the HA-receptor interaction remain to be clinically developed. Several reports are available on the in vitro activity of small-molecule inhibitors of influenza virus fusion, which act by preventing the conformational change of the HA at low pH Deshpande et al, 2001;Plotch et al, 1999). Unfortunately, their development has been slow due to their inferior activity against some human influenza virus (sub)types, rapid selection for resistance and/or unsatisfactory outcome in animal models (Yagi et al, 1999).…”
mentioning
confidence: 99%
“…By screening a chemical library, scientists at Wyeth-Ayerst Research have identified three compounds, CL61917 (an Nsubstituted piperidine), CL 385319 (the 5-fluoro analog of CL 61917), and CL62554 ( Fig. 5A), with inhibitory activity against H1 and H2 subtypes of IAVs with IC 50 at low micromolar levels (Plotch et al, 1999). Analysis of HA genes of the mutant viruses resistant to these compounds showed that single amino acid mutations clustered in the stem region of the HA trimer in and near the HA2 FP.…”
Section: Iav Fusion Inhibitors That Block the Ph-induced Conformationmentioning
confidence: 99%
“…Within the endosomal compartment, the virion is exposed to the increasing acid pH 5-6, the HA protein undergoes an irreversible conformation change from its metastable prefusion conformation to a low-pH hairpin structure involving extrusion of the "fusion peptide (FP)" from the interior of the HA2 at the neutral-pH structure toward the endosomal membrane, promoting fusion of the viral and endosomal membranes (Harrison 2008;Reed et al, 2010). Xray crystallographic studies have demonstrated the extensive rearrangement of residues in HA2 at low pH with respect to their relative orientation and coil-coil formation, loop-to-helix or helix-to-loop transitions (Bullough et al, 1994;Durrer et al, 1996;Plotch et al, 1999;Harrison 2008).…”
Section: Introductionmentioning
confidence: 99%